PELANGGARAN HAK CIPTA OLEH MAL GRAND INDONESIA DALAM PENGGUNAAN SKETSA TUGU SELAMAT DATANG - Jessica Edelina, (2022)
The definition of copyright is regulated in Law Number 28 of 2014 concerning Article 1 Number 1 concerning Copyright. There are two types of exclusive rights, namely moral rights and economic rights. But the fact is that there are still many people who violate copyright, not paying attention to the moral and economic rights of the creator or copyright holder. The sketch/picture is one of the works of art listed in the Copyright Law Number 28 of 2014 (UUHC) paragraph (1) Article 58, which is used by Grand Indonesia as a shopping center logo without permission from the copyright holder, therefore Grand Indonesia Shopping Center Indonesia Mall Indonesia was declared to have violated copyright, namely economic rights and non-personal property. The panel of judges at the Central Jakarta District Court later stated that the Grand Indonesia mall had to compensate 1 billion rupiah for the violation. The research method used in this study uses a normative juridical approach with an analytical approach using the provisions of the legislation relevant to the issues discussed. The results of the study show that copyright infringement is still rampant in Indonesia, so the government and the public need to be more concerned about copyright protection. An important conclusion from this research is that any copyright infringement committed will be subject to sanctions in accordance with applicable legal provisions, so that people need to respect and respect the creators of works of art so that there are no more copyright infringement. Keywords : Copyright, Sketch, Grand Indonesia Mall, Government, Society